(untitled) (Bangladesh Journal of Bioethics, 2014)
This is a review article prepared as a part of the assignment in the educational activity and training on research ethics titled Ethical and Regulatory Aspects of Clinical Research arranged by the Bangladesh Bioethics Society (BBS), Dhaka, Bangladesh, in collaboration with the Department of Bioethics of National Institutes of Health (NIH), Bethesda, Maryland, USA, through video conferencing between September 25 and November 13 of 2013. The search was confined to Google, HINARI and PubMed published articles. Besides, some guidelines on roles and responsibilities of Institutional Review Board (IRB) were taken into consideration. Key words used for searching were institutional review board, ethical review committee and ethical research. A total of 18 journal articles and some guidelines were selected for this writing. The systemic review from the databases revealed some important discussions on research, ethical research, roles and responsibilities of IRB/ERC and its challenges, and national/institutional research strategies. DOI: http://dx.doi.org/10.3329/bioethics.v5i1.18442 Bangladesh Journal of Bioethics 2014 Vol.5(1): 5-10